"Psychosomatic": a systematic review of its meaning in newspaper articles. - Stone, J; Colyer, M; Feltbower, S; Carson, A; Sharpe, M (2004)
In this study, the authors describe the meaning of the word "psychosomatic" in U.S. and U.K. newspaper articles using a systematic text word search and a consensus rating of the contextual meaning of all articles published in 14 U.S. and U.K. newspapers between 1996 and 2002. The survey was limited to broadsheet newspapers. "Psychosomatic" had a pejorative meaning, such as "imaginary" or "made up," in 74 of 215 (34%) of the articles in which the meaning could be judged. Most commonly, "psychosomatic" was used to describe a problem that was psychological or in which the mind affects the body (56%) rather than as a reciprocal interaction (5%). "Psychosomatic medicine" is the new name for the seventh subspecialty of psychiatry. More needs to be done to educate the media about its actual meaning to make it attractive to patients.